2023
DOI: 10.53623/idwm.v3i1.183
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in the Soil Around a Cement Company in Sokoto, Northwestern Nigeria Pose Health Risks

Abstract: Cement is widely used in the building industry because it is reliable and because its basic ingredients are inexpensive and abundant. However, the production of cement produces heavy metal-laden dust that can harm humans and the environment. This study aimed to determine the risk posed by heavy metals in the soil around a cement company in Sokoto, Nigeria. Soil samples were obtained at 0.1, 0.5, and 1.0 km from the company and served as test samples, while control samples were obtained at 5.0 km away. The soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…However, compared with the background values of the world average for soil, the mean concentrations of the investigated PTEs were lower than the world average elemental values [32]. The PTE concentrations observed in this study are lower than those reported outside Nigeria [29,[33][34][35] and in Nigeria [19][20][21]36], but in comparable with those at Karst, Brazil [37], Odajana, Nigeria [28], and Canakale-Ezine, Turkey [39] presented in (Table 2), which indicate that cement production activities had less in uence in the study areas. Moreover, it has been reported that an estimation of adverse health effects associated with PTEs, based on concentrations is not su cient and must be followed with other estimated indices [16].…”
Section: Concentrations Of Pte Occurrence In Soilscontrasting
confidence: 77%
See 1 more Smart Citation
“…However, compared with the background values of the world average for soil, the mean concentrations of the investigated PTEs were lower than the world average elemental values [32]. The PTE concentrations observed in this study are lower than those reported outside Nigeria [29,[33][34][35] and in Nigeria [19][20][21]36], but in comparable with those at Karst, Brazil [37], Odajana, Nigeria [28], and Canakale-Ezine, Turkey [39] presented in (Table 2), which indicate that cement production activities had less in uence in the study areas. Moreover, it has been reported that an estimation of adverse health effects associated with PTEs, based on concentrations is not su cient and must be followed with other estimated indices [16].…”
Section: Concentrations Of Pte Occurrence In Soilscontrasting
confidence: 77%
“…Moreover, studies of PTE concentrations and risk assessment on soils have been reported in Nigeria [12,[18][19][20][21]. However, limited or no study have been reported on geochemical, and risk assessments of the PTE study area.…”
Section: Introductionmentioning
confidence: 99%
“…Mining activities: artisanal gold mining and its associated risks: The allure of gold draws millions to artisanal mining, but its environmental and human health consequences are undeniable. Studies have highlighted the impact of illegal artisanal gold mining on heavy metal exposure to water bodies, leading to pollution and potential health risks (Olujimi et al, 2015;Edogbo et al, 2020;Yahaya et al, 2023). River basins and mining landscapes bear the brunt of this contamination, with heavy metals leaching into waterways, disrupting ecosystems, and jeopardizing aquatic life (Ouma et al, 2022;Orosun et al, 2023).…”
Section: Sources Of Heavy Metal Contaminationmentioning
confidence: 99%
“…The study focused on the seasonal concentrations of total and bioavailable heavy metals, along with the physicochemical properties of the soil in vegetable farms around the rock quarry. Yahaya et al (2023) conducted a study to assess the risk posed by heavy metals in the soil around a cement company in Sokoto, Nigeria. Soil samples were collected at different distances from the company, and the levels of lead (Pb), cadmium (Cd), copper (Cu), and zinc (Zn) were analyzed.…”
Section: Heavy Metals In Watermentioning
confidence: 99%
“…[1]. Thus, the cement manufacturing industry plays a vital role in global economic development [2]. In recent years, there has been a substantial surge in cement production, which can be attributed to increased commercialization, urbanization, population growth, and infrastructural development [3].…”
Section: Introductionmentioning
confidence: 99%